Tra argento, grano e panni Piero Pantella, un operatore italiano nella Ragusa del primo Quattrocento - Pinelli, Paola (Biblioteca di storia, 2013)
Placed in a favourable position between land and sea, in the XV century Ragusa (Dubrovnik) was the protagonist of the commercial exchanges in the Mediterranean and represented an important reference point for all the merchants who turned to Constantinople. There were three goods in particular around which the small Republic built its fortune, attracting the attention of many merchants (especially Italians): the silver from the Balkan mines, the Apulian wheat and woolen cloths. In this volume the reconstruction of the international dimension of Ragusa passes through the review of multiple studies, coming especially from the Slavic area, conducted during the second half of the twentieth century, supplemented by a rich unpublished public, notary and corporate documentation kept in the Ragusa and Italian archives. In particular, the accounting records and correspondence of Piero Pantella, a Piacenza merchant who moved to Ragusa in 1415, were taken into consideration, from which the significant commercial activity that the merchant carried out in the Dalmatian city emerges, but also the important role that he covered in the development of the Ragusa textile manufacture.